2019
DOI: 10.1186/s12911-019-0893-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between user interface problems of an admission, discharge and transfer module and usability features: a usability testing method

Abstract: Background The admission, discharge and transfer (ADT) module is used in the hospital information system (HIS) for the purposes of managing appointments, patient admission, daily control of hospital beds, planning surgery procedures, keeping up-to-date on patient discharges, and registering patient transfers within or outside the hospital. The present study aimed to evaluate the usability of ADT module of a HIS through usability testing and assess the relationship between the number of user interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
13
0
5
Order By: Relevance
“…The study by Khajouei et al [29] also reported that the HE method is signi cantly superior in identifying problems associated with satisfaction, which is consistent with the results of the present study, however, in the present study, satisfaction was at the second place, following effectiveness in terms of the usability attributes having the most number of recognized problems by the HE method. As a general rule, effectiveness can be achieved when users are able to perform their activities and tasks accurately and completely via the system [50,51]. As a result, correcting the recognized usability problems by the HE method leads to a signi cant increase in the effectiveness and satisfaction of users, provided that a system is well-designed with minimal complexity.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Khajouei et al [29] also reported that the HE method is signi cantly superior in identifying problems associated with satisfaction, which is consistent with the results of the present study, however, in the present study, satisfaction was at the second place, following effectiveness in terms of the usability attributes having the most number of recognized problems by the HE method. As a general rule, effectiveness can be achieved when users are able to perform their activities and tasks accurately and completely via the system [50,51]. As a result, correcting the recognized usability problems by the HE method leads to a signi cant increase in the effectiveness and satisfaction of users, provided that a system is well-designed with minimal complexity.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, researchers evaluated the usability of this HIS in performing these eight processes. [ 16 ]…”
Section: Methodsmentioning
confidence: 99%
“…According to the results, the effectiveness of this system was not different in the effectiveness of the paper-based system, but its efficiency was higher. Farrahi in a study [22] measuring the relationship between user interface problems of an admission, discharge, and transfer (ADT) module with usability attributes, found that the efficiency and effectiveness of that system were unacceptable. This was due to the user interface issues such as unclear function of some keys, lack of "help" option, and the existence of hidden menus in the system.…”
Section: Principal Findingsmentioning
confidence: 99%